Antecedents of Risky Financial Investment Intention among Higher Education Students: A Mediating Moderating Model Using Structural Equation Modeling - Ibrahim A. Elshaer; Abu Elnasr E. Sobaih (Mathematics, 2023)
The current study examines the direct effect of investment awareness and university education support on students’ risky financial investment intentions. Additionally, it examines the mediating effect of social influence and the moderating effect of self-control on these relationships. For this purpose, we directed an online questionnaire to senior students at three public universities in Saudi Arabia. The results of SmartPLS showed positive significant effects of investment awareness and university education support on social influence towards investment. The results also showed direct positive significant effects of investment awareness and university education support on students’ risky financial investment intentions. The results confirmed a partial mediating effect of social influence on the link between investment awareness and university education support on students’ risky financial investment intentions. Moreover, self-control was found to have a moderating effect on the link between investment awareness, university education support and social influence. Self-control failed to confirm the other moderating effects; i.e., the link between university education support and investment awareness, nor the link between investment awareness, university education support and risky financial investment intention. Implications of these findings for academics and policymakers to stimulate investment intention among higher education graduates in the Kingdom of Saudi Arabia (KSA) are discussed.